Observation of muon intensity variations by season with the MINOS near detector - Adamson, P; Anghel, I; Aurisano, A; Barr, G; Bishai, M; Blake, A; Bock, G; Bogert, D; Cao, S; Castromonte, C; Childress, S; Coelho, J; et al. (American Physical Society, 2014)
A sample of 1.53×109 cosmic-ray-induced single muon events has been recorded at 225 m water equivalent using the MINOS near detector. The underground muon rate is observed to be highly correlated with the effective atmospheric temperature. The coefficient αT, relating the change in the muon rate to the change in the vertical effective temperature, is determined to be 0.428±0.003(stat.)±0.059(syst.). An alternative description is provided by the weighted effective temperature, introduced to account for the differences in the temperature profile and muon flux as a function of zenith angle. Using the latter estimation of temperature, the coefficient is determined to be 0.352±0.003(stat.)±0.046(syst.). © 2014 American Physical Society.